Penerapan Manajemen Risiko Pembiayaan di BMT Maslahah, Cabang Pembantu Olean Situbondo - Subaidi Subaidi; Ikmalul Ihsan (Program Pascasarjana Universitas Ibrahimy, 2019)
BMT Maslahah Sub-Branch Olean in Situbondo still faces several problems and risks in providing financing to customers, because the customer intentionally does not return the financing he has obtained, even though he was able to repay the loan. This study focuses on how the applications of risk management in the financing, the causes and the solutions in BMT Maslahah Sub-Branch Olean of Situbondo. This study uses a qualitative approach with a case study strategy. Data collection is done by connecting questions with data obtained from conclusions from the interview of several persons in BMT Maslahah Sub-Branch Olean in Situbondo. The results of the study indicate that the risk of loss is the high number of problematic financing, starting from the difficulties and even payment defaults from customers caused by the loss of the ability of customers to pay installments and profit sharing to them. The effort carried out by them in saving the problematic financing is by rescheduling, reconditioning, and restructuring. They also cooperate with insurance companies to cover the losses.